Towards understanding the play of Atsimevu in Atsiã - Pantaleoni, Hewitt (International Library of African Music, 1972)
The Anlo (Eve) dance drumming orchestra of southeastern Ghana has three components, each with its own general level of pitch. In the highest range idiophones and the smallest of the drums play unchanging ostinati that provide the gait of the music. One of these high instruments controls the timing and placement of all patterns. In the middle range one or more drums support the musical gait of the upper range but with varied patterns. This intermediate drumming is also usually responsive to the third component, the leading drum (or master drum), which plays intermittently in the lowest range. Some of the play of the leading drum is decorative; some controls the performers with signals.
Keywords: Music; Drum; Ewe (African people); Dance; Ethnomusicology; Anlo (African people); Musical instruments; Drum music; Ghana; African Music; Drum (Instrument); Musical Meter; Musical Rhythm